1999
DOI: 10.1177/004051759906900306
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Moisture Vapor Transfer Through Textiles

Abstract: This study investigates the influence of semipermeable functional films on the sur face vapor pressure and temperature of fabric-film-fabric assemblies. The film added between two fabric layers affects vapor pressure and temperature changes on both surfaces of the assembly under simulated body-clothing conditions. The physical char acteristics of films greatly influence the level of transient, comfort-related variables such as changes of inner surface vapor pressure and temperature. Mixed cotton and polyester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…While diffusion along fibers is a smaller contributor to overall diffusion, it is believed to have a significant impact on thermal comfort. [68] Absorption describes the ability of the textile to allow moisture vapor to enter into its volume. Adsorption, on the other hand, is the migration of water vapor along the surface of the textile.…”
mentioning
confidence: 99%
“…While diffusion along fibers is a smaller contributor to overall diffusion, it is believed to have a significant impact on thermal comfort. [68] Absorption describes the ability of the textile to allow moisture vapor to enter into its volume. Adsorption, on the other hand, is the migration of water vapor along the surface of the textile.…”
mentioning
confidence: 99%
“…The outer layer of protective clothing is generally coated with microporous PU or laminated with PTFE films, which restrict water penetration, while allowing for the passage of water vapor. It has been found that in microporous membrane samples (e.g., Gore-Tex) the physical characteristics such as film pores or fabric air spaces are far more important to the moisture transfer of the fabric-film-fabric assembly than the hydrophilicity of the film [4]. These type of fabrics obey Fick's law of diffusion, wherein diffusion coefficient 'D' does not alter with changes in the water vapor concentration within the polymer or with changes in temperature.…”
Section: Measurement Of Water Vapor Transmission Of Fabricsmentioning
confidence: 99%
“…In fact, the evaporation of sweat from the skin surface interferes with clothing and thus insufficient evaporation often creates a sense of discomfort when wearing inadequate clothing. 14 When wearing clothing, heat and moisture produced by the body are stopped at a layer of air before passing into the environment, resulting in the characteristic microclimate between the skin and clothing, which affects the sense of comfort. The temperature and humidity on the skin surface are the parameters that are dependent on the environment (climate) parameters and clothing, such as the properties of fabrics and garments' openness.…”
mentioning
confidence: 99%